2007
DOI: 10.1148/radiol.2451061116
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided Detection of Colorectal Polyps: Can It Improve Sensitivity of Less-Experienced Readers? Preliminary Findings

Abstract: Results of this feasibility study suggest that CAD for CT colonography significantly improves per-polyp detection for less-experienced readers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 45 publications
4
51
2
Order By: Relevance
“…Recently, Halligan et al [13] demonstrated that second-read CAD also benefits the experienced CTC reader, finding that mean per-polyp sensitivity for polyps 6 mm or larger increased on average by 9%. As expected, additional interpretation of CAD candidates extends overall CTC reading time by a few minutes [12,14]. 3) "Concurrent" CAD.…”
Section: How To Use Cadmentioning
confidence: 69%
See 1 more Smart Citation
“…Recently, Halligan et al [13] demonstrated that second-read CAD also benefits the experienced CTC reader, finding that mean per-polyp sensitivity for polyps 6 mm or larger increased on average by 9%. As expected, additional interpretation of CAD candidates extends overall CTC reading time by a few minutes [12,14]. 3) "Concurrent" CAD.…”
Section: How To Use Cadmentioning
confidence: 69%
“…Intuitively, second-read CAD should be most beneficial when adopted by less experienced readers; radiologists relatively unfamiliar with CTC have lower detection rates and their gain when using CAD should be larger than for experienced readers [11]. Baker et al [12] have shown that, for polyps 6 mm or larger, second-read CAD improves detection of readers with some or no experience in CTC reporting from 81% to 91%. These authors also found that CAD second-read increases detection of intermediate size polyps.…”
Section: How To Use Cadmentioning
confidence: 99%
“…Several CTC studies in which the additional value of CAD was evaluated (after the interaction with the observer) have reported good results in terms of polyp detection [12,[25][26][27]. All concluded that the observers detected statistically more polyps with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies concluded that in a selected population CAD significantly improved per-polyp sensitivity for less experienced observers [10][11][12][13]. Though experienced observers benefited proportionally less from CAD [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomographic colonography (CTC) or virtual colonoscopy has been widely used for detecting colorectal neoplasms via 3D computed tomography (CT) abdomen scans of the cleansed and air-distended colon. In the last decade, many computer aided detection and diagnosis systems [4,5,6,7] have been proposed and actively studied to improve the performance and reliability of human radiologists as second readers.…”
Section: Introductionmentioning
confidence: 99%